Electrochemical oxidation of pyrite in pH 2 electrolyte. (10th June 2017) - Tu, Zhihong; Wan, Jingjing; Guo, Chuling; Fan, Cong; Zhang, Ting; Lu, Guining; Reinfelder, John R.; Dang, Zhi
Highlights: Electrochemical oxidation of pyrite occurred by two reaction pathways. At potential of 0.50 V, electrochemical oxidation of pyrite was diffusion-limited. At potential of 0.60 V, amorphous S8 was slowly converted to crystalline S8 . S8 was difficult to be oxidized electrochemically even at high potential. Oxidation of pyrite was inhomogeneous on electrode surface. Abstract: The oxidation of pyrite under acidic conditions, an important process leading to the formation of acid mine drainage, has been the subject of intense research yet remains incompletely understood. In this study, the mechanism of the electrochemical oxidation of pyrite in a pH 2 electrolyte was investigated using electrochemical techniques. The morphological changes and oxidation products of pyrite were studied using atomic force microscopy (AFM), Raman spectroscopy (RS), and X-ray photoelectron spectroscopy (XPS). At low potential of 0.50 V, electrochemical oxidation of pyrite was diffusion-limited due to a sulfur-rich layer (S 0 ) that formed and covered the pyrite surface, resulting in surface passivation. As the potential increased to 0.60 V, diffusion-limitation and surface passivation of pyrite oxidation ceased due to the conversion of amorphous elemental sulfur (S8 ) to crystalline S8, resulting in the previously covered active sites being re-exposed which allowed continued oxidation of pyrite. At higher potentials of 0.70 and 0.80 V, more S8 and polysulfides (Sn 2− ), together with an iron-rich layer composed of Fe(OH)3, FeO and Fe2 O3, formed and accumulated on the pyrite surface. These products led to a decreased rate of oxidation rather than a complete passivation of the surface. AFM imaging revealed that surface roughness increased with oxidation potential and that the oxidation of the pyrite surface was inhomogeneous. These findings provide further insight into the physical and chemical changes that pyrite undergo during electrochemical oxidation, which deepens our understanding of this important process.